THE SOCIO-CULTURAL ENVIRONMENT, PARENTAL PERCEPTION, ADOLESCENT KNOWLEDGE, AND ATTITUDE TOWARD EARLY-AGE MARRIAGE DECISION - Nona Intan Permatasari Wadjaudje; Nisaul Habibah; Laili Rahayuwati; Tetti Solehati (Journal of Maternity Care and Reproductive Health, 2019)
The relatively high number of early-age marriages in Indonesia, committed by 60.000 couples under 18 in West Java, even rises from 53 to 117 in 2015. The socio-cultural environment and parents are the most influential factor in early-age marriages, particularly in villages. However, limited studies determine the social influence on young women decision including deciding early marriage. The research objectives were to identify the socio-cultural environment and parental perception toward early marriage decision, and describing how adolescent knowledge and attitude toward early-age marriages. The research design is cross sectional study. The sample is taken using proportionate cluster random sampling, consisting of 144 parents, and 250 adolescents. The result shows that the socio-cultural environment (47.2%), and parental perception (62.4%), low level of knowledge (44%) and positive attitude (52.4%) to postpone early-age marriage. It can be concluded that the strength of cultural value plays a vital role in the population's health decision. Therefore, it is necessary to develop a program between the government and the healthcare community to overcome early-age marriage issues.Keywords: Adolescent knowledge, attitude, parental perception.